Shifting sands: A bibliometric analysis of L2 vocabulary research in 1991 - Meara, Paul (LingBaW. Linguistics Beyond and Within, 2023)
This paper uses a co-citation analysis to examine the research on L2 vocabulary acquisition that was published in 1991. Two analyses based on co-citations in this research are presented. The first analysis provides a context for the 1991 data. It looks at work that was being cited in a five-year window covering 1987-1991. The second analysis is a more detailed account of the 1991 research on its own terms.